1998
DOI: 10.1097/00001888-199806000-00015
|View full text |Cite
|
Sign up to set email alerts
|

What students say about learning and teaching in longitudinal ambulatory primary care clerkships

Abstract: Students perceived that learning during longitudinal ambulatory clerkships had greater impact on skill enhancement than on attainment of knowledge-related objectives. Sources of variation in student opinion, perceptions of learning as a function of career preference, and correlation of students' perceptions of learning to demonstrable changes in their competence require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Wilson & Cleland 2008) understanding that the learning outcomes were the same as those of students undertaking traditional block rotations if such activities were running in parallel. Some outcomes were very broad and more related to program objectives rather than assessable outcomes, for example: integration of basic and clinical science (Bell 2008), humanism in patient care (Bell et al 2008;Couper & Worley 2010), concepts relating to the doctor-patient relationship (Lewin et al 1999;Carney et al 2005), primary care needs of rural, underserved communities (Florence et al 2007;Halaas et al 2008), development of insights into community-based Bell et al 2008;Berger & Schaffer, 1986;Denz-Penhey et al 2004;Hadac et al 1979;Hamilton et al 1998;Henley et al 2000;Hirsh et al 2012;Lemon et al 1995;Lewin et al 1999;Lubetkin et al 1999;Ogur et al 2007;Peters et al 2001;Poncelet et al 2011;Poole et al 2010;Prislin et al 1998;Ringdahl et al 2009;Schauer & Schieve, 2006;Stagg et al 2009;Verby 1988;von Below et al 2008;Wee et al 2011;Wilson & Cleland, 2008 Student 1:1 interviews 14 Couper et al 2011;Denz-Penhey et al 2004Denz-Penhey & Murdoch 2008;Hamilton et al 1998;Hauer et al 2012;Walmsley et al 2009;W...…”
Section: What Learning Outcomes/objectives Are Defined?mentioning
confidence: 99%
“…Wilson & Cleland 2008) understanding that the learning outcomes were the same as those of students undertaking traditional block rotations if such activities were running in parallel. Some outcomes were very broad and more related to program objectives rather than assessable outcomes, for example: integration of basic and clinical science (Bell 2008), humanism in patient care (Bell et al 2008;Couper & Worley 2010), concepts relating to the doctor-patient relationship (Lewin et al 1999;Carney et al 2005), primary care needs of rural, underserved communities (Florence et al 2007;Halaas et al 2008), development of insights into community-based Bell et al 2008;Berger & Schaffer, 1986;Denz-Penhey et al 2004;Hadac et al 1979;Hamilton et al 1998;Henley et al 2000;Hirsh et al 2012;Lemon et al 1995;Lewin et al 1999;Lubetkin et al 1999;Ogur et al 2007;Peters et al 2001;Poncelet et al 2011;Poole et al 2010;Prislin et al 1998;Ringdahl et al 2009;Schauer & Schieve, 2006;Stagg et al 2009;Verby 1988;von Below et al 2008;Wee et al 2011;Wilson & Cleland, 2008 Student 1:1 interviews 14 Couper et al 2011;Denz-Penhey et al 2004Denz-Penhey & Murdoch 2008;Hamilton et al 1998;Hauer et al 2012;Walmsley et al 2009;W...…”
Section: What Learning Outcomes/objectives Are Defined?mentioning
confidence: 99%
“…Medical students are on the wards seeing patients and attending the RMO ward rounds, and are therefore in uenced to a greater extent by RMOs than faculty members, because of the greater time spent together (Sheets et al, 1991). In support of this observation, it is reported that students are reported to obtain approximately one third of their knowledge during clinical clerkships from RMOs (Sheets et al, 1991;Bing-You & Tooker, 1993) and student feedback has been used to provide insights into the effectiveness of resident rotations (Prislin et al, 1998). This proximity allows both formal and informal teaching, and therefore we wished to investigate whether student learning could be facilitated, and if it would be successful.…”
Section: Introductionmentioning
confidence: 96%
“…13 Proponents of a longitudinal curriculum have also upheld the value of learning the natural history of a disease from a patient firsthand and forming a relationship with a patient rather than focusing learning on a complaint or disease. 14 Many programs have implemented longitudinal preceptorships with a goal of teaching about continuity of care, but logistical challenges may prevent implementation for some medical schools. 1,2 Limited reports have described what students learn about continuity of care in longitudinal preceptorships that attempt to teach about continuity of care.…”
Section: Medical Student Educationmentioning
confidence: 99%
“…Others have surveyed students about skills and knowledge they acquired in longitudinal rotations. 14 At the University of Washington, preclinical medical students participate in an 8-12 week preceptorship during their first year. One purpose of this experience is to provide early exposure to patients and engage students in a dialogue about the utility of continuity of care.…”
Section: Medical Student Educationmentioning
confidence: 99%